Examining Deixis in Zakir Naik's Preaching Videos: A Pragmatic Analysis - Tanjung, Muhammad Rafiq; Muslim, Ahmad Bukhori (Indonesian Journal of EFL and Linguistics, 2025)
As a popular and important field in pragmatic study, deixis has been largely investigated by many researchers across disciplines and in various types of discourse. However, its use in Islamic discourse focusing on comparative religion is rarely explored. Therefore, this study examined deictic expressions used in Islamic public oration by a famous scholar. Employing a descriptive qualitative method, it aims to find out the main types of deixis, focusing on the analysis of the frequency, what they refer to, & the functions. The data were gained from a corpus of three recorded preaching sessions available online on YouTube. The findings showed that personal deixis becomes the most dominant type, followed by spatial and temporal deixis. Personal deixis mainly worked to refer to the addressee & to engage the addressee in the discourse. It also referred to the preacher as a form of revealing his identity. Then, spatial deixis functioned as a way to focus the talk to particular things and to refer to preceding or following ideas or acts. In addition, temporal deixis was primarily used to refer to present times, showing the high relevance of the discourse with current moments. This paper is hoped to provide insights regarding how deixis serves various crucial functions in preaching and how it facilitates the speaker to persuade the addressee to the explanations given. Hence, the results of this study could inform those who aspire to be a better speaker by practicing using deictic expressions more properly to sound more convincing.